Edna St. Vincent Millay papers - Millay, Edna St. Vincent, 1892-1950.; Boissevain, Eugen, -1949.; Millay, Cora Buzzell; Millay, Norma; Milholland, Inez.
Correspondence, diaries, notebooks, literary drafts, reports, family papers, legal and financial records, scrapbooks, theatrical playbills, photographs, and other papers relating chiefly to Millay's life and literary career. Topics include her travels, daily life especially at her Steepletop farm in Austerlitz, N.Y., theater groups such as the Provincetown Players, politics, totalitarianism, and World War II.
Papers of her mother, Cora Buzzell Millay, reflect Cora's literary ambitions and efforts; the careers and activities of her daughters, Edna St. Vincent Millay, Kathleen Millay, and Norma Millay including their participation in avant-garde or experimental theater and antiwar socialist politics; and genealogy of the Buzzell and Emery families. Norma Millay's papers document her work as literary executor of Edna St. Vincent Millay's estate. Also includes papers of Edna St. Vincent Millay's husband, Eugen Boissevain, and of his first wife, Inez Milholland, and correspondence of the Boissevain family.
Other correspondents include Millay's father, Henry T. Millay; her aunts, Clementine Buzzell Parson and Susan Buzzell Ricker; and Millay's sister, Kathleen, and brother-in-law, Howard Irving Young; and Millay's sister Norma Millay's husband, Charles Ellis.
Library of Congress Rare Book and Special Collections Division.
Library of Congress Prints and Photographs Divison.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Library of Congress Serial & Government Publications Division.
Poet and author.
Collection material in English, French, and Dutch.
Keywords: Millay, Edna St. Vincent, -- 1892-1950 -- Travel; Millay, Henry T. -- Correspondence; Millay, Kathleen, -- -1943 -- Correspondence; Parson, Clementine Buzzell -- Correspondence; Ricker, Susan Buzzell -- Correspondence; Young, Howard Irving, -- 1893- -- Correspondence; Boissevain family -- Correspondence; Buzzell family -- Genealogy; Emery family -- Genealogy; Millay family; Provincetown Players; Experimental theater; Literature; Peace movements; Poetry; Socialism -- United States -- History -- 20th century; Theater -- United States -- History -- 20th century; Totalitarianism; World War, 1939-1945.; Austerlitz (N.Y.) -- Social life and customs; United States -- Politics and government -- 20th century; Authors; Poets